PENGARUH MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA QUIZIZZ TERHADAP BERPIKIR KRITIS DAN KETERAMPILAN SOSIAL SISWA KELAS V PADA PEMBELAJARAN IPAS - Hartini, Sri Hastuti Anwa; Na’im, Mohamad; Alfarisi, Ridho; Nuriman, Nuriman; Hilmi, Muhammad Irfan (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to: (1) examine the effect of Quizizz-assisted cooperative learning on the critical thinking skills of fifth-grade elementary students in IPAS learning; and (2) analyze its effect on students’ social skills. This research was classified as an experimental study conducted at SDN Sawaran Kulon 02, Kedungjajang District, Lumajang Regency. The population consisted of all fifth-grade students, with 19 students in class VA and 21 students in class VB, totaling 40 students. The study employed a pretest–posttest control group design, in which two classes were randomly assigned as the experimental and control groups. Based on theoretical review, relevant studies, and data analysis, the findings indicate that the implementation of Quizizz-assisted cooperative learning had a positive effect on both students’ critical thinking skills and social skills. In conclusion: (1) there is a significant effect of Quizizz-assisted cooperative learning on students’ critical thinking skills in IPAS learning; and (2) there is also a significant effect on students’ social skills.